Relations Gln27Glu polymorphism β2-adrenoceptor gene with bronchial asthma - А. N. Bondarkova; L. N. Prystupa; V. G. Psareva (Zaporožskij Medicinskij Žurnal)
Purpose – to analyze scientific literature data on the link between Gln27Glu polymorphism gene of β2-adrenergic receptors development and bronchial asthma (BA) severity, level of control.